从《史记·汲郑列传》管窥太史公之史法与笔法 = A restricted view on SIMA Qian’s historical method and writing technique from Ji An & Zheng Dangshi, Memoir 60 - 曲景毅 Qu, Jingyi (Chinese Literature and History Press, 2017)
一、《史记·汲郑列传》之史法与笔法。 二、《史记·汲郑列传》与《汉书·张冯汲郑传》之对读。